A single‐population GWAS identified AtMATE expression level polymorphism caused by promoter variants is associated with variation in aluminum tolerance in a local Arabidopsis population. (12th August 2020) - Nakano, Yuki; Kusunoki, Kazutaka; Maruyama, Haruka; Enomoto, Takuo; Tokizawa, Mutsutomo; Iuchi, Satoshi; Kobayashi, Masatomo; Kochian, Leon V.; Koyama, Hiroyuki; Kobayashi, Yuriko
Abstract: Organic acids (OA) are released from roots in response to aluminum (Al), conferring an Al tolerance to plants that is regulated by OA transporters such as ALMT (Al‐activated malate transporter) and multi‐drug and toxic compound extrusion (MATE). We have previously reported that the expression level polymorphism (ELP) of AtALMT1 is strongly associated with variation in Al tolerance among natural accessions of Arabidopsis. However, although AtMATE is also expressed following Al exposure and contributes to Al tolerance, whether AtMATE contributes to the variation of Al tolerance and the molecular mechanisms of ELP remains unclear. Here, we dissected the natural variation in AtMATE expression level in response to Al at the root using diverse natural accessions of Arabidopsis. Phylogenetic analysis revealed that more than half of accessions belonging to the Central Asia (CA) population show markedly low AtMATE expression levels, while the majority of European populations show high expression levels. The accessions of the CA population with low AtMATE expression also show significantly weakened Al tolerance. A single‐population genome‐wide association study (GWAS) of AtMATE expression in the CA population identified a retrotransposon insertion in the AtMATE promoter region associated with low gene expression levels. This may affect the transcriptional regulation of AtMATE by disrupting the effect of a cis‐regulatory element located upstream of the insertion site, which includes AtSTOP1 (sensitive to proton rhizotoxicity 1) transcription factor‐binding sites revealed by chromatin immunoprecipitation‐qPCR analysis. Furthermore, the GWAS performed without the accessions expressing low levels of AtMATE, excluding the effect of AtMATE promoter polymorphism, identified several candidate genes potentially associated with AtMATE expression.